Kinematic alterations due to different loading schemes in early acceleration sprint performance from starting blocks - Maulder, P. S.; Bradshaw, E. J.; Keogh, J. W. L. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to examine the changes to block start and early acceleration sprint kinematics with resisted sled towing. Ten male sprinters performed 12 sprints (four each of unresisted and approximately 10 and 20% body mass [BM]) for 10 m from a block start. Two-dimensional high-speed video footage (250 Hz) of the starting action and the first three steps of each sprint were recorded to enable the sagittal sprinting kinematic parameters to be obtained using APAS motion analysis software. The overall results of this study indicated that early acceleration sprint performance from starting blocks decreases with increasing load during resisted sled towing. A load of approximately 10% BM had no "negative" effect on sprint start technique or step kinematic variables measured in this study (with the exception of one variable) and was also within the "no greater than 10% decrease in speed" limits suggested by Jakalski. Towing a load of approximately 20% BM increased the time spent in the starting blocks and induced a more horizontal position during the push-off (drive) phase. The approximately 20% BM load also caused the sprinters to shorten their initial strides (length), which may have resulted from the decreased flight distances. Such results suggest that the kinematic changes produced by the 10% BM load may be more beneficial than those of the 20% BM load. Future training studies will, however, need to investigate how these acute changes in sprinting technique impact on long-term adaptations in sprinting performance from resisted sprinting.